A comparative study of the effect of conventional hemodialysis versus hemodiafiltration on the eye - Hesham E. Abdalmonem; Hosny A. Younos; Aldosoky Abd Elaziz Alsaid; Ahmed A. Abdelgbar; Ayman Abdelaziz (Al-Azhar Assiut Medical Journal)
Background and aim Hemodiafiltration (HDF) seems to be the gold standard concerning dialysis-aided renal replacements. Hemodialysis (HD) and severe renal failure both have visual side effects, including high intraocular pressure, band keratopathy, macular leakage, red eyes, retinal hemorrhage, and optical neuropathy. The purpose of this study is to examine the impact of routine conventional HD versus routine HDF on ocular problems in individuals with chronic kidney disease (CKD). Patients and methods This prospective cross-sectional observational study was conducted on 200 patients divided into 100 patients of CKD on regular HD three times weekly (4 h duration) (HD group) and 100 patients of CKD on regular HDF three times weekly (4 h duration) (HDF group). clinical interview, routine laboratory tests, and complete eye examination were done on all participants. Results Prior to treatment, there was no significant difference between the HDF and HD categories for either eye’s central foveal thickness, average macular thickness, visual acuity, intraocular pressure, anterior segment, or fundus examination. In addition, no significant difference was observed between both groups after therapy in both eyes. Conclusion Regular HDF and HD treatments administered for 6 months each had no negative impact on ocular parameters.